2013
DOI: 10.12691/ajbr-1-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Physiological Determinants of Pulmonary Developmental Biology: a Review

Abstract: The lungs undergo an extensive endodermal diverging morphogenesis along with alveogenesis, angiogenesis, and vasculogenesis to secure a sufficient diffusion surface for gaseous exchange. Any aberration in the course of normal development inculcating structural and functional abnormalities of lungs in antenatal life has potential morbidity in adult life. Factors such as IUGR, nutrient deficiency, FLM, Hypoxemia, ETS, surfactant deficiency, allergy and infections can adversely affect in-utero lungs development. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 214 publications
(228 reference statements)
0
6
0
Order By: Relevance
“…OP pesticides can readily pass through the placenta ( Rauh et al 2006 ; Whyatt et al 2009 ), and DAP metabolites can be found in amniotic fluid ( Bradman et al 2003 ). Furthermore, during the second half of pregnancy the alveoli are forming and surfactant is being synthesized; lung surfactant dysfunction is known to be related to the pathophysiology of asthma ( Hameed et al 2013 ; Wright et al 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…OP pesticides can readily pass through the placenta ( Rauh et al 2006 ; Whyatt et al 2009 ), and DAP metabolites can be found in amniotic fluid ( Bradman et al 2003 ). Furthermore, during the second half of pregnancy the alveoli are forming and surfactant is being synthesized; lung surfactant dysfunction is known to be related to the pathophysiology of asthma ( Hameed et al 2013 ; Wright et al 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Addressing the multitude of molecular determinants of pulmonary development in detail would greatly strain the capacity of this review. A summary is given in Figure and greater details are explained, for example, in Cardoso (), McMurtry (), Roth‐Kleiner and Post (), and Hameed et al, ().…”
Section: Lung Functional Developmentmentioning
confidence: 99%
“…It is known that the expression of these mediators is directly or indirectly related to sialic acid content. 6,34,41 In human fetuses, a slight decrease in total sialic acid expression was reported to occur in lung epithelial structures during intra-uterine development with a relative minimum before birth. An increased expression of sialic acid residues during development of alveoli and differentiation of pneumocytes I and pneumocytes II -with the latter expressing high amounts of sialic acids -was also described.…”
Section: Discussionmentioning
confidence: 99%
“…However, during alveolarization, rat lung undergoes similar modifications as those of humans, making rats one of the most useful animal models in this field. 6 Alveolarization comprises a biphasic behavior with a first phase termed classical or "bulk" alveolarization, in which alveoli are formed apace, and a second phase, named continued alveolarization, which involves a slower formation of alveoli. These phases overlap and, in rats, the first phase elapses from postnatal day 4 to day 14 (P4-P14).…”
Section: Introductionmentioning
confidence: 99%